IMPLEMENTASI METODE PICTURE EXCHANGE COMMUNICATION SYSTEM (PECS) DALAM PENINGKATAN KEMAMPUAN KOMUNIKASI ANAK AUTIS “AU” DI DESA CILEUNYI KULON KECAMATAN CILEUNYI KABUPATEN BANDUNG - Rosilawati Rosilawati (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2022)
Autistic children often experience communication problems so they must receive special training. This study aims to determine the characteristics of research subjects, namely autistic children with the initials AU, the condition of AU's communication skills before and after the implementation of the Picture Exchange Communication System (PECS) method. The research method is a single subject experimental design A-B-A which shows a causal relationship between the dependent variable and the independent variable. The results showed that the characteristics of AU had experienced an inability to communicate since the age of two years due to family disharmony. In addition to not being able to speak verbally, the AU's communication skills before the implementation of PECS experienced non-verbal limitations. AU's non-verbal communication skills are measured through the ability to recognize objects, recognize images of objects, receive verbal messages and convey messages through pictures. Of the sixteen objects introduced, namely plates, spoons, forks, glasses, towels, soap, toothbrushes, brooms, books, ballpoint pens, colored pencils, scissors, erasers, knives, blankets and pillows, the AU only responded to 8 types of objects. AU's ability after implementing PECS is that AU recognizes 16 types of objects and images of objects and is able to receive all verbal messages through these images. However, the AU knows some of the objects (5 objects) they want and hand them over to the researcher, namely books, towels, plates, glasses, and spoons. The conclusion of the study shows that the implementation of PECS for the ability to recognize objects, recognize object images, receive verbal messages and through images is able to change AU's communication skills from moderate to low to high abilities. However, the AU's ability to convey messages through images is in the moderately low category